Voice of America in the Classroom: Assessing Its Educational Value for Listening Comprehension in High School English Classes - Ayuaneka, Debi; Sujarwati, Iis (Indonesian Journal of English Language Studies (IJELS), 2025)
This study examines the relationship between the use of Voice of America (VOA) videos and students' listening comprehension in English language courses through a mixed-methods explanatory sequential design, addressing the ongoing debate on the effectiveness of authentic media in language learning. Given the increasing reliance on digital content for language acquisition, this study explores whether VOA videos offer measurable advantages over traditional listening materials in debating issues: why is it significant? The research includes quantitative data collection involving listening comprehension tests and surveys with Likert-scale questionnaires, followed by qualitative data gathered through structured interviews. Quantitative analysis using SPSS and Pearson correlation indicates a weak positive relationship between VOA video use and listening performance (r = 0.108, p = 0.651), which is statistically insignificant. Qualitative insights suggest that VOA videos provide exposure to authentic pronunciation, intonation, and accents, and may contribute to increased motivation for learning. Thematic analysis identifies challenges, such as the speed of speech and the presence of technical terminology. In general, the students' listening comprehension scores showed improvement, with a median score of 80/100. The findings suggest that integrating authentic video materials like VOA into language instruction may have pedagogical value while also highlighting limitations for broader applicability.